Oral Manifestations of Rett Syndrome—A Systematic Review - Mahdi, Syed Sarosh (Int J Environ Res Public Health, 2021)
Rett Syndrome is an x linked developmental disorder which becomes apparent in females after 6 to 18 months of age. It leads to severe impairments including loss of speech, loss of hand movements/manual dexterity, characteristic hand movements such as hang wringing and intellectual disability/learning problems. This systematic review was carried out to identify the dental manifestation of Rett syndrome and to shed light on treatment options available for oral health problems associated with Rett syndrome. A systematic literature search was conducted on the PubMed, Scopus, Biomed, Web of Science, Embase, Google Scholars, Cochrane and CINAHL using the following entries: Rett syndrome (n = 3790), Oral health and Rett syndrome (n = 17), dental health of Rett syndrome patients (n = 13), and the MeSH terms listed below: Rett syndrome and Oral Health (n = 17), Rett syndrome and dentistry (n = 29). The final review included 22 search articles. The most common oral findings was bruxism. Masseteric hypertrophy was also reported. Anterior open bite and non-physiological tooth wear was observed. Other oral manifestations of Rett syndrome included mouth breathing, tongue thrusting, digit/thumb sucking, high arch palate. Increased awareness and dental education amongst dentists and assistants regarding the dental manifestations of Rett syndrome and similar neurodevelopmental disorders is required to improve the level of care and empathy they can provide to these differently able patients. Research on dental aspects of Rett is scarce and this remains a neglected topic.